2010
DOI: 10.1111/j.1467-8624.2010.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Child Care and the Development of Behavior Problems Among Economically Disadvantaged Children in Middle Childhood

Abstract: Research examining the longer term influences of child care on children’s development has expanded in recent years, but few studies have considered low-income children’s experiences in community care arrangements. Using data from the Three-City Study (N = 349), this study examines the influences of child care quality, extent and type on low-income children’s development of behavior problems during middle childhood (7–11 years old). Higher levels of child care quality were linked to moderate reductions in exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 53 publications
2
52
2
1
Order By: Relevance
“…We found that children in higher risk families (i.e., low income and high family dysfunction) seem to especially benefit from high quality care. This finding is consistent with past findings that higher quality care may serve as a protective factor for at-risk children (Love et al, 2003;McCartney et al, 2003;Votruba-Drzal et al, 2010). As Votruba-Drzal and colleagues (2010) explain, low-income children, faced with limited resources in their home environments, may be especially responsive to the added supports of stimulating and responsive non-parental care or, conversely, the added risks of poor quality child care.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that children in higher risk families (i.e., low income and high family dysfunction) seem to especially benefit from high quality care. This finding is consistent with past findings that higher quality care may serve as a protective factor for at-risk children (Love et al, 2003;McCartney et al, 2003;Votruba-Drzal et al, 2010). As Votruba-Drzal and colleagues (2010) explain, low-income children, faced with limited resources in their home environments, may be especially responsive to the added supports of stimulating and responsive non-parental care or, conversely, the added risks of poor quality child care.…”
Section: Discussionsupporting
confidence: 93%
“…First, data were drawn from a nationally-representative sample of Canadian children, thereby increasing the generalizability of our findings, as well as offering valuable knowledge regarding experiences that may be unique to Canadian child care settings. Second, past research on the long-term influence of child care has tended to use broad behavioral categories such as internalizing and externalizing behaviors (e.g., Côté et al, 2008;NICHD ECCRN, 2005) or has investigated externalizing behaviors exclusively (e.g., McCartney et al, 2010;Votruba-Drzal et al, 2010). Our focus on more specific behaviors allowed us to make finer distinctions regarding the ways in which child care might differentially impact specific child behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Higher quality care has been shown to be an especially strong protective factor against the development of behavior problems for African American children (Burchinal, Roberts, Zeisel, Hennon, & Hooper, 2006;Votruba-Drzal, Coley, Maldonado-Carreno, Li-Grining, & Chase-Lansdale, 2010). Findings regarding the timing of care have been less straightforward; for example, kindergarten teacher ratings of African American children's social skills were positively associated with the number of years children had been in child care but negatively associated with the number of hours per week they had been in care since birth (Connell & Prinz, 2002).…”
Section: Child Care and Social Competencementioning
confidence: 93%
“…The CBCL is a 112-item instrument with internalizing and externalizing subscales as well as a composite or total problems scale. The CBCL has been validated on a number of samples and is a standard measure of externalizing behavior in children (Gross et al, 2006; Qi & Kaiser, 2003; Votruba-Drzal, Coley, Maldonado-Carreño, Li-Grining, & Chase-Lansdale, 2010). The CBCL has also been validated with under-represented populations including minority populations such as African-Americans and Hispanics (Gross et al, 2006).…”
Section: Methodsmentioning
confidence: 99%